Current understanding of IgA antibodies in the pathogenesis of IgA nephropathy - Nihei, Yoshihito; Suzuki, Hitoshi; Suzuki, Yusuke (Frontiers in Immunology, 2023)
Immunoglobulin A (IgA) is the most abundant isotype of antibodies; provides a first line of defense at mucosal surfaces against pathogens and thereby contributes to mucosal homeostasis. IgA is generally considered as non-inflammatory antibody because of its main function, neutralizing pathogenic virus or bacteria. Meanwhile, IgA can induce IgA-mediated diseases, such as IgA nephropathy (IgAN) and IgA vasculitis. IgAN is characterized by the deposition of IgA and complement C3, often with IgG and/or IgM, in the glomerular mesangial region, followed by mesangial cell proliferation and excessive synthesis of extracellular matrix in glomeruli. Almost half a century has passed since the first report of patients with IgAN, it remains debatable about the mechanism how IgA antibodies selectively bind to mesangial region—a hallmark of IgAN— and cause glomerular injuries in IgAN. Previous lectin- and mass-spectrometry-based analysis have revealed that IgAN patients showed elevated serum level of undergalactosylated IgA1 in O-linked glycans of its hinge region, called galactose-deficient IgA1 (Gd-IgA1). Thereafter, numerous studies have confirmed that the glomerular IgA from IgAN patients are enriched with Gd-IgA1; thus, the 1st hit of the current pathogenesis of IgAN have been considered to be increased circulating levels of Gd-IgA1. Recent studies, however, demonstrated that this aberrant glycosylation alone is not sufficient to disease onset and progression, suggesting that several additional factors are required for selective deposition of IgA in mesangial region and inducing nephritis. Herein, we discuss the current understanding of the characteristics of pathogenic IgA and its mechanism of inducing inflammation in IgAN.